Maternal obesity remodels the maternal intestinal microbiota and is associated with altered maternal intestinal and placental function - Wallace, Jessica G. (My University, 2016)
The prevalence of overweight and obesity have risen to epidemic proportions. Overweight and obesity are prominent risk factors for the development of chronic disease including diabetes, cardiovascular disease and cancer. Especially pronounced in women of reproductive age and children, the obesity epidemic represents a major threat to global health. Maternal obesity is a key predictor of childhood obesity and diseases of metabolic origin in adulthood. Previous work has demonstrated that the exposure to early life adversity, in the context of maternal obesity, is associated with an increased risk of metabolic disease and obesity in the offspring later in life. Although the mechanisms outlining the relationship between maternal and offspring obesity remain unclear, the intestinal microbiota has come forth as a promising area of research. To understand the factors involved in the maternal intestinal microbial shifts with healthy pregnancy, the preliminary study focused on investigating whether female sex-steroid hormones mediate maternal intestinal microbial shifts in non-pregnant, regularly cycling female mice. We have identified that intestinal microbial shifts are not associated with sex-steroid hormone fluctuations. The second study examined whether maternal intestinal microbial shifts that occur during obese pregnancy were associated with altered inflammatory signaling and function of the maternal intestine and placenta at a critical period of development; embryonic (E) day 14.5. Females fed a high fat diet (HFD) were significantly heavier at mating and throughout gestation compared to CON. At E14.5, High fat (HF) dams displayed increased adiposity, hyperglycemia, hyperinsulinemia, hyperleptinemia and were insulin resistant. Pregnancy and maternal obesity resulted in shifts in the maternal intestinal microbiota, where the most significant increase in microbial relative abundance was exhibited by the mucin degrading genus, Akkermansia. At E14.5, maternal intestinal microbial shifts were associated with higher maternal intestinal NFκB activity in all sections of the maternal intestine, most notably in the maternal colon. Maternal obesity was associated with increased Muc5ac mRNA levels and a modest increase in CD3+ T cells in the maternal colon at E14.5. However, maternal intestinal permeability was unchanged between groups. In the placenta, mRNA levels of key signaling components in the pro-inflammatory toll-like receptor 4 (TLR4) pathway; TRAF6, NFκB and potent pro-inflammatory cytokine TNF-α were increased and in HF females. Maternal obesity was associated with an increase in CD3+ T cells in the junctional zone (JZ), but not in the labyrinth zone (LZ) of the placenta at E14.5. These findings were associated with increased mRNA levels of critical nutrient transporters; glucose transporter 1 (GLUT1) and sodium-coupled neutral amino acid transporter 2 (SNAT2) and a modest increase in glucose transporter 3 (GLUT3) in HF placentae compared to CON. These data identify the mechanistic signaling pathways and cell types involved in modulating the intrauterine environment, thus contributing to the current literature devoted to the investigation of the developmental origins of obesity.
Keywords: Maternal obesity, Pregnancy, Intestinal microbiota, Placenta, Developmental origins of health and disease